Konstruksi Sosial Citra Universitas pada Mahasiswa Dalam Memilih Studi di Perguruan Tinggi - Prayoga Putra Aditya; A. Octamaya Tenri Awaru; Muhammad Syukur (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
There are many factors that influence the formation of the image of prospective students. This research is a qualitative research that aims to analyze the image of the university in the new students of the Makassar State University and the social construction of the image of the university in the new students. The informants were selected by purposive sampling technique, namely the new students of Makassar State University and made Makassar State University the first choice. Interviews and documentation were used as data collection techniques and then analyzed through three stages, namely data reduction, data presentation and conclusion drawing. The data obtained were checked for validity using the member check technique. The results of the study found that: 1) a positive image of Makassar State University was formed for new students in the form of: a. Complete facilities and infrastructure; b. Qualified teaching staff; c. And many alumni are absorbed in the world of work. 2) the social construction of a positive image of Makassar State University is formed through three simultaneous processes, namely externalization, objectivation, and internalization. The formation of the construction is influenced by social media, family, community and school.